This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The contrapositive of a conditional statement is logically equivalent to the original statement but with the antecedent and consequent "flipped" and negated. Thus the contrapositive of p ⟹ q is ~ q ⟹ ~ p .
The converse of a conditional statement involves a flip of the antecedent and consequent. Thus the converse of ~ q ⟹ ~ p is ~ p ⟹ ~ q .
Finally, the inverse of a conditional statement involves the negation of the antecedent and the consequent. Thus the inverse of ~ p ⟹ ~ q is
~(~ p ) ⟹ ~(~ q ) , which is the same as p ⟹ q .
The more things change, the more they stay the same ......